2022
DOI: 10.3390/brainsci12040455
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of a Simultaneous Exercise and Cognitive Task on Executive Functions and Prefrontal Cortex Oxygenation in Healthy Older Adults

Abstract: The rapid increase in population aging and associated age-related cognitive decline requires identifying innovative and effective methods to prevent it. To manage this socio-economic challenge, physical, cognitive, and combined stimulations are proposed. The superiority of simultaneous training compared to passive control and physical training alone seems to be an efficient method, but very few studies assess the acute effect on executive function. This study aimed to investigate the acute effect of simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The distance between each emitter and receptor was 3.5 cm. The placement of this patch was already used in previous studies [ 69 , 70 ]. The sensors were shielded from ambient light with a black cloth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The distance between each emitter and receptor was 3.5 cm. The placement of this patch was already used in previous studies [ 69 , 70 ]. The sensors were shielded from ambient light with a black cloth.…”
Section: Methodsmentioning
confidence: 99%
“…During all the procedure, our participants were asked to always face forward during the test, avoid making a sudden head movement, clenching their jaw, frowning, and other facial expressions. This pre-processing analysis was already used in previous studies [ 70 ]. To analyze the fNIRS results, we first performed a channel-by-channel analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CMDT training has emerged as an intervention strategy that combines cognitive and motor training. It has been shown that CMDT training may be more effective as an effective combined intervention than a single training modality (Pellegrini-Laplagne et al, 2022). (Oswald et al, 2006;Gallou-Guyot et al, 2020b).…”
Section: Current Interventions For Arcimentioning
confidence: 99%